Diet, alcohol, and relative weight in gall stone disease: a case-control study. Issue 6424 (14th April 1984) - Scragg, R K; McMichael, A J; Baghurst, P A
Abstract : A case control study of gall stone disease in relation to diet, alcohol, and relative weight was undertaken. The study population comprised 267 hospital patients with newly diagnosed gall stone disease, 241 individually matched controls selected from the community, and 359 controls who were patients in hospital. Dietary intake was estimated with a quantitative food frequency questionnaire. Multiple logistic regression analysis was used to estimate the net association between individual nutrients and the risk of formation of gall stones. Variations in risk with sex and age were examined in the light of prior evidence of influences of sex hormones and age on hepatobiliary metabolism. In both sexes increased intake of alcohol was associated with a decreased risk of developing gall stones; increased intake of simple sugars in drinks and sweets was associated with an increased risk; and increased intake of energy or fat was associated with an increased risk in young subjects. Obesity was associated with an increased risk only in young women.